2015
DOI: 10.11648/j.ijepp.20150306.12
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting Smallholder Farmers’ Tradeoffs and Preferences on the Attributes of Climate Smart Agriculture in the Breadbasket Areas of Tanzania Using a Conjoint Experiment Method

Abstract: While policy and decision-makers are striving to enhance food security amidst maddening impacts of climate change, climate smart agriculture is thought of as a promising breakthrough for responding to climate change impacts in Tanzania and elsewhere in the world as it strives to increase food productivity; build resilience of agricultural systems to climate change impacts and reduce agricultural greenhouse gas emission. Studies show that agricultural sector is both, a cause and a victim of climate change. It s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 9 publications
2
5
1
Order By: Relevance
“…However, low climate resilience agriculture, high GHG emission, low crop yield and organic fertilizers as supplementary production input showed a negative utility. This result is also supported by Mussa et al (2015), who revealed that low and moderate agricultural productivity, high GHG emission and low resilience farming systems showed negative utility value.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…However, low climate resilience agriculture, high GHG emission, low crop yield and organic fertilizers as supplementary production input showed a negative utility. This result is also supported by Mussa et al (2015), who revealed that low and moderate agricultural productivity, high GHG emission and low resilience farming systems showed negative utility value.…”
Section: Discussionsupporting
confidence: 65%
“…This result is also supported by Mussa et al . (), who revealed that low and moderate agricultural productivity, high GHG emission and low resilience farming systems showed negative utility value.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations